Chromatin as a sensor of metabolic changes during early development - Pladevall-Morera, David; Zylicz, Jan J. (Frontiers in Cell and Developmental Biology, 2022)
Cellular metabolism is a complex network of biochemical reactions fueling development with energy and biomass; however, it can also shape the cellular epigenome. Indeed, some intermediates of metabolic reactions exert a non-canonical function by acting as co-factors, substrates or inhibitors of chromatin modifying enzymes. Therefore, fluctuating availability of such molecules has the potential to regulate the epigenetic landscape. Thanks to this functional coupling, chromatin can act as a sensor of metabolic changes and thus impact cell fate. Growing evidence suggest that both metabolic and epigenetic reprogramming are crucial for ensuring a successful embryo development from the zygote until gastrulation. In this review, we provide an overview of the complex relationship between metabolism and epigenetics in regulating the early stages of mammalian embryo development. We report on recent breakthroughs in uncovering the non-canonical functions of metabolism especially when re-localized to the nucleus. In addition, we identify the challenges and outline future perspectives to advance the novel field of epi-metabolomics especially in the context of early development.